2015
DOI: 10.1371/journal.pone.0131707
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Vascular Calcification Scores to Traditional Risk Factors Improves Cardiovascular Risk Assessment in Patients with Chronic Kidney Disease

Abstract: BackgroundAlthough a variety of non-invasive methods for measuring cardiovascular (CV) risk (such as carotid intima media thickness, pulse wave velocity (PWV), coronary artery and aortic calcification scores (measured either by CT scan or X-ray) and the ankle brachial index (ABI)) have been evaluated separately in chronic kidney disease (CKD) cohorts, few studies have evaluated these methods simultaneously. Here, we looked at whether the addition of non-invasive methods to traditional risk factors (TRFs) impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…Data are expressed as medians (interquartile ranges) or number (percentages) or as mean ± SD risk factors, our data showed that high CAC scores remained strongly associated with CIN. Moreover, recent studies reported that the addition of vascular calcification scores to traditional cardiovascular risk factors increased the predictive abilities for all-cause and cardiovascular outcomes in CKD populations [21,22]. In the present study, we demonstrated that clear relationships with the finding that the model with both CAC scores and MRS could more accurately predict CIN incidence with an increased C-index.…”
Section: Discussionsupporting
confidence: 70%
“…Data are expressed as medians (interquartile ranges) or number (percentages) or as mean ± SD risk factors, our data showed that high CAC scores remained strongly associated with CIN. Moreover, recent studies reported that the addition of vascular calcification scores to traditional cardiovascular risk factors increased the predictive abilities for all-cause and cardiovascular outcomes in CKD populations [21,22]. In the present study, we demonstrated that clear relationships with the finding that the model with both CAC scores and MRS could more accurately predict CIN incidence with an increased C-index.…”
Section: Discussionsupporting
confidence: 70%
“…200,201 Data from a post hoc analysis of 8 studies evaluating individuals in the general population receiving high-intensity statin therapy have recently suggested that statins may actually increase vascular calcification and in so doing may stabilize otherwise unstable plaques. 202 Statins have not been conclusively shown to reduce CVD events in patients with ESRD; however, medial rather than intimal calcification predominates in patients with kidney disease.…”
Section: Emerging Diagnostic Tools and Therapies Vascular Calcificationmentioning
confidence: 99%
“…High serum phosphorus levels can promote the transformation of vascular smooth muscle cells into osteoblasts to increase bone calcium mobilization. Consequently, intercellular and intracellular calcium concentrations are increased, resulting in calcium phosphorus deposition in the atherosclerotic plaque and arterial muscle layer, which promotes CAC (15). Moreover, coronary angiography results from 32 patients showed that the rate of multi-vessel disease directly correlated with the CAC score, whereas single-vessel disease did not correlate with the CAC score.…”
Section: Discussionmentioning
confidence: 99%